Incompatibility, product attributes and consumer welfare: evidence from ATMs - Christopher R. Knittel; Victor Stango (University of California, Department of Economics, 2005)
Incompatibility in market with network effects reduces consumers? ability to ?mix and match? components offered by different sellers, but can also spur changes in product attributes that might beneÞt consumers. In this paper, we estimate the effects of incompatibility on consumers in a classic hardware/software market: ATM cards and machines. We Þnd that while ATM fees ceteris paribus reduce the network beneÞt from other banks? ATMs, a surge in ATM deployment accompanies the shift to surcharging. This is valuable to consumers and often completely offsets the harm from higher fees. The results suggest that policy discussions of incompatibility must consider not only its direct effect on consumers, but also its effect on product attributes.
Keywords: 330